Adult Drosophila sensory neurons specify dendritic territories independently of dendritic contacts through the Wnt5-Drl signaling pathway. - Yasunaga, K.; Tezuka, A.; Ishikawa, N.; Dairyo, Y.; Togashi, K.; Koizumi, H.; Emoto, K. (Genes & Development, 2015)
Sensory neurons with common functions are often nonrandomly arranged and form dendritic territories in stereotypic spatial patterns throughout the nervous system, yet molecular mechanisms of how neurons specify dendritic territories remain largely unknown. In Drosophila larvae, dendrites of class IV sensory (C4da) neurons completely but nonredundantly cover the whole epidermis, and the boundaries of these tiled dendritic fields are specified through repulsive interactions between homotypic dendrites. Here we report that, unlike the larval C4da neurons, adult C4da neurons rely on both dendritic repulsive interactions and external positional cues to delimit the boundaries of their dendritic fields. We identify Wnt5 derived from sternites, the ventral-most part of the adult abdominal epidermis, as the critical determinant for the ventral boundaries. Further genetic data indicate that Wnt5 promotes dendrite termination on the periphery of sternites through the Ryk receptor family kinase Derailed (Drl) and the Rho GTPase guanine nucleotide exchange factor Trio in C4da neurons. Our findings thus uncover the dendritic contact-independent mechanism that is required for dendritic boundary specification and suggest that combinatory actions of the dendritic contact-dependent and -independent mechanisms may ensure appropriate dendritic territories of a given neuron.